Effects of gasifying agent on the evolution of char structure during the gasification of Victorian brown coal - Tay, Hui-ling; kajitani, Shiro; Zhang, Shu; Li, Chun-Zhu (Elsevier Science Ltd, 2013)
Steam plays a vital role in the gasification process. This study aims to investigate the changes in charstructure and reactivity during the gasification of Victorian brown coal. A Loy Yang brown coal samplewas gasified at 800 C in a novel fluidised-bed/fixed-bed reactor in three different gasification atmospheres: 15% H2O balanced with argon, 4000 ppm O2 balanced with CO2 and 4000 ppm O2 + 15% H2O balanced with CO2. The intrinsic reactivities of chars with air were measured with a thermogravimetric analyser (TGA) at low temperatures (380 or 400 C). The char structural features were characterised using FT-Raman spectroscopy followed by spectral deconvolution. Our results indicate that steam, when it is present in the gasifying atmosphere, has a drastic effect on char structure and the subsequent reactivity of char with air at low temperatures. The presence of steam during the gasification at 800 C also impacts on the volatilisation of Mg and Ca by altering the char structure. Our data provide evidence that the char–H2O gasification follows a different reaction pathway from the char–CO2 gasification, at least for the gasification of Victorian brown coal under the current experimental conditions.